The value of liver stiffness measured by two-dimensional shear wave elastography for predicting symptomatic posthepatectomy liver failure in patients with hepatocellular carcinoma. Issue 150 (May 2022) - Shi, Yifan; Long, Haiyi; Zhong, Xian; Peng, Jianyun; Su, Liya; Duan, Yu; Ke, Weiping; Xie, Xiaoyan; Lin, Manxia
Highlights: The best cutoff value of LS for predicting symptomatic PHLF was 9.5 kPa. The predictive performance of LS was higher than that of a diagnosis of CSPH. The predictive performance of LS was comparable to that of pathological fibrosis stage. Abstract: Purpose: To assess and compare the value of liver stiffness measurement (LSM) by two-dimensional shear wave elastography (2D-SWE) with the diagnosis of clinically significant portal hypertension (CSPH) and pathological examination in predicting symptomatic posthepatectomy liver failure (PHLF) in patients with hepatocellular carcinoma (HCC). Method: A total of 130 patients who underwent liver resection for HCC between August 2018 and July 2021 were enrolled. Preoperative assessments for LSM and other clinicopathological tests were performed in all patients. The performance of LSM, CSPH and fibrosis stage in predicting symptomatic PHLF was assessed and compared. Univariate and multivariate analyses were conducted on the risk factors for symptomatic PHLF. Results: Symptomatic PHLF occurred in 40 patients (30.8%). The best LSM cutoff value for predicting symptomatic PHLF was 9.5 kPa. The areas under the receiver operating characteristic curve (AUCs) of LSM ≥ 9.5 kPa, fibrosis stage and CSPH for predicting symptomatic PHLF were 0.732 (95% CI: 0.638–0.826, p < 0.001), 0.655 (95% CI: 0.553–0.758, p = 0.005) and 0.594 (95% CI: 0.484–0.705, p = 0.086), respectively. The AUC of LSM ≥ 9.5 kPa was significantly higher than that of CSPH ( p = 0.010), and was comparable to that of fibrosis stage ( p = 0.073). Multivariate analysis identified LSM ≥ 9.5 kPa ( p = 0.001), major hepatectomy ( p = 0.007) and CSPH diagnosis ( p = 0.040) as independent predictors of symptomatic PHLF. Conclusions: LSM by 2D-SWE was promising for predicting symptomatic PHLF in HCC patients. The predictive performance was higher than that of CSPH and comparable to that of pathological fibrosis stage.